The Role of Quality of Work Life as a Predictor of Counterproductive Work Behavior - P. Tommy Y. S. Suyasa (ANIMA Indonesian Psychological Journal, 2017)
Counterproductive work behavior (CWB) is work behavior that violates the rules/norms (written or unwritten) that could potentially harm an organization or members of an organization. This study aimed to explain CWB based on the condition of the quality of work life (QWL). CWB can be negative behavior towards co-workers/supervisors/subordinates in the workplace (CWB-I) and can be either negative behavior towards tasks/rules/organizational system (CWB-O). Participants in this study were the members of National Police. The number of participants was 305 people. Based on the analysis, the better the quality of relationships with supervisors (supervisory), the implementation of work culture (constitutionalism), the quality of relationships with co-workers (co-worker), and the quality of tasks/responsibilities (promotion), the lower the CWB-I. Meanwhile, the lower levels of CWB-O were predicted by the promotion of quality of relationships with supervisors (supervisory). The study raised a further question concerning why the higher quality of/balance between work and private life (work life balance) led into the higher levels of CWB-I.